2020
DOI: 10.1002/cam4.3331
|View full text |Cite
|
Sign up to set email alerts
|

PI16 attenuates response to sorafenib and represents a predictive biomarker in hepatocellular carcinoma

Abstract: Liver cancer is reported as the sixth most commonly diagnosed malignancy and the fourth leading cause of cancer-related deaths worldwide in 2018, with approximately 841 000 new diagnoses and 782 000 deaths every year.(1) Hepatocellular carcinoma (HCC) comprises more than 75% of all liver cancers.(1) Partial hepatectomy and liver transplantation remain the most effective treatment for patients with HCC. However, due to the late symptom presentation and aggressive tumor biological behavior, many patients with HC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Crawford et al found that overexpression of Pi16 significantly inhibited breast cancer tumorigenesis and metastasis 32 . Wang et al found that knocking down Pi16 could significantly inhibit apoptosis and thus increase the sensitivity of hepatocellular carcinoma to sorafenib therapy 10 . In addition, Pi16 works through multiple pathways, such as regulating the activation of p53 signaling pathways or acting as a protease inhibitor of cathepsin K and MMP2 33 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Crawford et al found that overexpression of Pi16 significantly inhibited breast cancer tumorigenesis and metastasis 32 . Wang et al found that knocking down Pi16 could significantly inhibit apoptosis and thus increase the sensitivity of hepatocellular carcinoma to sorafenib therapy 10 . In addition, Pi16 works through multiple pathways, such as regulating the activation of p53 signaling pathways or acting as a protease inhibitor of cathepsin K and MMP2 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that Pi16 is expressed in a variety of tissues, including cardiomyocytes, the digestive tract, and the testes, and is involved in a variety of pathophysiological processes, including fibrosis, immune regulation, and signal transduction 7–9 . In recent years, studies have shown that Pi16 can regulate the occurrence and metastasis of tumors by targeting the p38/MAPK pathway, the NEMO/NF‐κB axis, or other mechanisms 10,11 . In addition, Pi16, as an independent risk factor for prognostic judgment, has certain value in guiding the clinical treatment of prostate cancer and hepatocellular carcinoma 10,12 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…scorpions, Cid-Uribe et al, 2018 ). Whereas its role in venoms is still unknown, in humans PI16 expression has been connected to conditions including heart disease ( Frost & Engelhardt, 2007 ), cancer ( Wang et al, 2020 ), and inflammation ( Hazell et al, 2016 ). PI16 prevents the proteolytic activation of chemerin, a protein involved in recruiting macrophages to sites of inflammation ( Regn et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al recently published their data about the role of PI16, a gene with differential expression in many tumor cells; low levels of PI16 were significantly associated with longer PFS and OS in patients treated with sorafenib, suggesting its possible value as a predictive biomarker [ 105 ].…”
Section: Unmet Needs and Future Perspectivesmentioning
confidence: 99%